Evaluating the in vitro activity of cefoperazone-sulbactam against Gram negative pathogens in blood stream infections using automated systems - Uksim Qadri; Sofiya Zaffar; Saleem Javaid Wani; Shugufta Roohi; Munazah Aman; Sabah Bhat; Umaya Majid (Iranian Journal of Microbiology)
Background and Objectives: The incidence of multidrug-resistant, Gram-negative organisms, isolated as the etiological agents of infections is ascending. The advent of novel antibiotics poses significant challenges, necessitating the optimization and utilization of extant antimicrobial agents. Cefoperazone, a third-generation cephalosporin and β-lactam antimicrobial, when combined with sulbactam, an irreversible β-lactamase inhibitor, mitigates the vulnerability of cefoperazone to β-lactamase-producing organisms. Nonetheless, regional data on the susceptibility patterns for this pharmacological combination remains scarce. The primary objective of this investigation was to assess the efficacy of the cefoperazone-sulbactam combination against prevalent Gram-negative bacteria isolated from blood cultures. Materials and Methods: A total of 700 Gram-negative isolates, comprising Escherichia coli, Klebsiella pneumoniae, Acinetobacter species, and Pseudomonas aeruginosa, were procured using the BacT/Alert 3D system. The identification and susceptibility testing for cefoperazone-sulbactam were performed using the VITEK Compact ID and AST system. Comparative analysis was conducted against other tested antibiotics. Results: The study revealed that cefoperazone-sulbactam exhibited commendable in-vitro activity against Gram-negative pathogens isolated from blood, surpassed only by colistin and tigecycline. Conclusion: Cefoperazone-sulbactam demonstrates robust activity against the most frequently encountered clinical pathogens, suggesting its potential as an efficacious therapeutic agent. The findings underscore the imperative for ongoing surveillance of resistance patterns and trends among commonly used antimicrobials.